Understanding the role of emotional intelligence and work status in service sabotage: Developing and testing a three-way interaction model. (December 2019) - Tao, Chen-Wei (Willie); Jang, Jichul; Kwon, Junehee
Abstract: Restaurant frontline employees who are the victims of customer mistreatment frequently engage in service sabotage. However, the boundary condition of the relationship between customer mistreatment and service sabotage behaviors remains unanswered. Drawing upon the conservation of resources and affective information processing theories, we propose that the effects of customer mistreatment on service sabotage behaviors vary as a function of the level of emotional intelligence and work status. Data collected from 210 non-managerial frontline employees in full-service restaurants were analyzed. Results reveal that emotional intelligence moderates the relationship between customer mistreatment and service sabotage behaviors. Moreover, work status moderates the relationship between customer mistreatment and service sabotage behaviors. However, the three-way interactions were not statistically supported. This study contributes to the body of service sabotage literature and yields practical implications for managing service sabotage in the restaurant industry.